Base insertion and deletion mutations induced in an Escherichia coli plasmid by benzo[a]pyrene-7,8-dihydrodiol-9,10-epoxide. - Mizusawa, H (1981)
Mutations induced by (+/-)trans-benzo-[a]pyrene-7,8-dihydrodiol-9,10-epoxide (BaP-diol epoxide-1) were selected by using a recombinant plasmid vector system designed for the study of transcription termination signals. The plasmid contains a transcription terminator positioned between a promotor signal and the Escherichia coli galactokinase structural gene (galK). By selections for the expression of galK (i.e., galK- to galK+), mutations are obtained in the terminator region that allow transcription from the promotor to read the galK gene. These mutations were characterized by direct DNA sequence of the terminator region. The DNA sequence changes caused by BaP-diol epoxide-1 were demonstrated for three different mutants. Two were found to be single-base-pair insertions of T.A into a cluster of consecutive T.A base pairs and the other change was a single-base-pair deletion of G.C from a cluster of consecutive G.C base pairs.